PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PT MAYORA INDAH TBK PERIODE 2013 – 2022 - Marlinda Fibriana, Wirda; Surahman, Arif (Journal of Research and Publication Innovation, 2024)
This study aims to examine the effect of profitability and liquidity on the company value of PT Mayora Indah Tbk which is listed on the Indonesia Stock Exchange for the period 2013-2022. The population in this study is the entire financial report of PT Mayora Indah Tbk which is listed on the Indonesia Stock Exchange 2013 - 2022. Sample the research used in this research is in the form of a balance sheet financial report and profit and loss financial report of PT Mayora Indah Tbk which is listed on the Indonesia Stock Exchange for the period 2013 - 2022. The analytical method used is quantitative descriptive with the data analysis technique used is the classic assumption test, multicollinearity , heteroscedasticity, normality test, correlation and determination coefficient test, simultaneous test and partial test using SPSS 26. The results of the t-test research show a sig value of 0.148 > 0.05 and the tcount value is smaller than ttable or 1.624 < 2.364 so it can be concluded that Return On Asset has no significant effect on Earning Per Share and the sig value is 0.033 > 0.05 and the tcount value is smaller than ttable or 2.642 > 2.364 so it can be concluded that the Current Ratio has a significant effect on Earning Per Share while the f-test results show Fcount 8,353 > Ftable 4.74 with a significance level of 0.014 which is smaller than a significance level of 0.05. so that Return On Asset s (ROA) and Current Ratio (CR) together (simultaneously) have a significant effect on Earning Per Share (EPS) .